Haematological Response of Pre-pubertal Rabbit Bucks Fed Cottonseed Cake-based Diets Supplemented with Vitamin E - Amao, O.A.; Adejumo, D.O.; Togun, V.A.; Oseni, B.S.A.; Fagbayila, E.B. (Pakistan Journal of Nutrition, 2012)
An investigation was conducted in a 2 x 4 factorial experiment to evaluate the effect of Cottonseed Cake (CSC) with or without vitamin-E supplementation on the haematological parameters of pre-pubertal rabbit bucks. The experiment involved 8 treatment combinations comprising four CSC levels (0, 5, 10 and 15%) and two vitamin-E supplementation levels (0 and 30 mg/kg diet) denoted as minus (-) vitamin-E and plus (+) vitamin-E. A feeding trial lasted for eight weeks after which blood was collected from the animals and analyzed for Haemoglobin concentration (Hb), Packed Cell Volume (PCV), Red Blood Cell Count (RBC) and White Blood Cell Count (WBC). Analysis of variance showed that CSC had significant (p0.05) HB, PCV and RBC while only WBC was significantly (p